Report of Working Group on Dredging Facilities for Ninth Five Year Plan (1997-2002) - Planning Commission (Planning Commission, 1996)
The modern dredgers are equipped with latest electronic equipment such as Global Position Fixing Systems, Production Metres, Echo Sounders PC's etc. These systems are required to be maintained by the crew on board the dredgers for their effecient functioning. Presently, the task is looked after by Electrical Officers who are not qualified in Electronics. The Committee suggests a minimum of two officers with Electronics and Electrical background to be posted on the dredgers.
Planning Commission
Government of India Planning Commission
Keywords: Preamble; Constitution of the Working Group; Meetings and Deliberations; Eighth Plan Targets and Lessons Drawn; Productivity Norms; Development Programme during Ninth plan; Role of Private Sector in dredging industry; Technological Development and R & D support; Comparative Cost of Dredging by 1 1 1 1 DCI and Port - Owned Dredgers; Internal Resources of DCI during Ninth Plan; Manpower Development for Dredging Industry; Excess Manpower in Ports and DCI